Mothers’ Hand washing Practice and Diarrhea Cases in Children under Five in Baleendah, Bandung - M Syafril Firdaus; Insi Farisa Desy Arya; Dadang Hudaya Somasetia (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Diarrhea is a disease, especially in children, with high mortality and morbidity rate in developing countries, including Indonesia. Diarrhea can be prevented if people can apply clean and healthy behaviors, especially hand washing. Hand washing is the cheapest, simplest, and the most effective methods for prevention of diarrhea. The objective of this study is to identify the knowledge, attitude, and practice of mothers’ hand washing and diarrhea cases in children under five in Baleendah District, Bandung.Methods: A descriptive study was conducted during September−November 2012 to 210 mothers who had children (ages 12−59 months) in Baleendah using rapid survey technique. The time allocated for each village was adjusted to the population proportion for each region. The data were analyzed using computerand was represented using frequency distribution.Results: This study showed that the respondents had good level of knowledge and attitude of hand washing (83.8% and 61%, respectively), but only 21% of the respondents’ practices of hand washing was in good level. Most of the respondents did not wash their hands according to the 7 steps of correct hand washing. Moreover the percentage of children with diarrhea in Baleendah was 43.8% (92 cases) during the study.Conclusions: There should be dissemination of information about the benefit of washing hands with 7 steps of correct hands washing so that families can practice it and can prevent diarrhea in children under five. [AMJ.2015;2(1):191–8]